Innovation of guided inquiry IPA wave module using PhET simulation - Saputri, Nurma Meinda Ira; Rosa, Friska Octavia; Partono (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
This study is an ADDIE model- based development research aiming to develop and validate a guided inquiry-based science practicum module integrated with PhET Simulation on wave concepts for junior high school students. The research subjects were eighth-grade students at SMPN 9 Metro. The module was designed to address limitations in laboratory facilities and students' difficulties in comprehending abstract concepts. The development process was limited to the development phase, involving validation by material and media experts. Data were collected through quantitative descriptive assessment using a Likert scale instrument. The final product contains structured practicum activities aligned with guided inquiry syntax, supplemented with interactive simulations to support student comprehension. Validation results indicate that the module is highly feasible for use, with an average feasibility percentage of 97.4%. Feedback from validators strengthened the module's refinement, particularly in terms of appearance, clarity of instructions, and media integration. The combination of the inquiry approach and PhET Simulation not only supports independent learning but also helps students visualize wave concepts more concretely and engagingly. This module is recommended as an innovative learning media alternative that can encourage scientific literacy and strengthen 21st-century skills. The theoretical contribution of this study is the strengthening of the foundation for developing digital simulation-based and guided inquiry learning. Furthermore, the availability of a valid module that can be directly applied in junior high school science instruction represents the practical contribution of this research.